Crystal structure of (E)-2,4-di-tert-butyl-6-(((2-fluorophenyl)imino) methyl)phenol, C21H26FNO - Zhao Wen-Ze; Tian Huan (Zeitschrift für Kristallographie - New Crystal Structures)
C21H26FNO, orthorhombic, Pna21 (no. 33), a = 12.329(3) Å, b = 9.048(3) Å, c = 16.881(5) Å, β = 90°, V = 1883.2(9) Å3, Z = 4, R gt(F) = 0.0500, wR ref(F 2) = 0.1184, T = 273(2) K.